2016
DOI: 10.1177/1074840716642790
|View full text |Cite
|
Sign up to set email alerts
|

A Family Systems Nursing Approach for Families Following a Stroke

Abstract: Stroke in midlife is a life altering, challenging experience for the whole family thereby necessitating a family approach to intervention. The aim of this study was to describe the experiences of 17 family members living in Sweden, including seven adult stroke patients (six males; one female) under the age of 65 who participated in a series of three nurse-led family conversations that were offered in each family's home. These Family Health Conversations (FamHC) were guided by the conceptual lens of Family Syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(74 citation statements)
references
References 43 publications
2
69
0
3
Order By: Relevance
“…They interpreted this as the fact that telling the story opened up for hope in the family. Experiences from the FamHC in the same sample as in the present study [28] have shown that room for narratives and deeper conversations were created within the conversations so in that sense the potential for families to develop hope is there. In the qualitative findings in the present study, even if not talking explicitly about hope, a reappraisal of life was found.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…They interpreted this as the fact that telling the story opened up for hope in the family. Experiences from the FamHC in the same sample as in the present study [28] have shown that room for narratives and deeper conversations were created within the conversations so in that sense the potential for families to develop hope is there. In the qualitative findings in the present study, even if not talking explicitly about hope, a reappraisal of life was found.…”
Section: Discussionmentioning
confidence: 73%
“…Moreover, there was room for creating confirmation. [28] It might be that these new and positive ways of communicating were kept in their own dialogues within the family after the intervention was concluded. Also, Dorell et al [26] have shown within the context of residential care, that one month after participating in FamHC there was an increase in the communication within the family.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this model, the family is seen as a system of relationships organized according to certain common goals that would not be reached separately by the different members (9) . The family is considered as a unique system that cannot be described by the sum of its parts, hence the group responses and not the individual responses were considered.…”
Section: Methodsological Proceduresmentioning
confidence: 99%